Energy-expending behaviour in frightened caribou when dispersed singly or in small bands - Blehr, Otto (Rangifer, 1997)
The behaviour of single, and small bands of caribou (Rangifer tarandus groenlandicus) when confronted by humans was compared with the energy—saving behaviour zoologists have ascribed to caribou in encounters with non-hunting wolves (Canis lupus). When confronted by me, or upon getting my scent, caribou ran away on all occasions. Their flight was occasionally interrupted by short stops to look back in my direction, but would continue on all occasions until they were out of sight. This behaviour is inconsistent with the one ascribed to caribou by zoologists when the intruder is a wolf instead of a human. In their view, the caribou stop their flight soon after the wolf gives up the chase, and accordingly save energy owing to their ability to distinguish between hunting and non-hunting wolves. However, small bands of caribou, as well as single animals, have never been observed to behave in this manner. On the contrary, the behaviour of caribou in such encounters is known to follow the same pattern as in their encounters with humans. Energy—saving behaviour is, however, sometimes observed when caribou become inquisitive about something in their surroundings. They will then readily approach as well as try to get down-wind of the object. When the object does not induce fear, it may simply be ignored, or charged before the caribou calm down. The effect of this "confirming behaviour" is that energy which would otherwise have been spent in needless flights from non-predators is saved.
Keywords: Rangifer; wolves; anti-predator behaviour; energy expenditure; Greenland